Foreigners Laws = مجموعة قوانين الأجانب. (2025)
D.NO. OF THE TEAR 1999 IN RESPECT OF THE ORGANIZATION OF PROCEDURES FOR OBTAINING A MORE PERMIT -- D.NO. 43 FOR 1988 IN CONNECTION WITH THE CONDITIONS OF WORK -- PERMITS FOR FOREIGNERS -- LAN NO. 56 FOR THE YEAR 1988 REGULATING THE PROPRIETOR- SHIP OF TILE NON-EGYPTIANS OF CONSTRUCTED REAL ESTATES AND DESERT LANDS -- D.NO. 25 FOR 1982 CONCERNING THE CONDITIONS FOR ISSUE OF WORK PERMITS FOR ALIENS -- D.NO. 2 OF 1979 ON THE EMPLOYMENT OF FOREIGN EXPERTS -- HOW TO OBTAIN A WORK PERMIT AND RESIDENCE FOR FOREIGN ERS WITHIN THE COUNTRY -- APPLICATION FOR A WORK LICENCE OR RENEWAL -- GUIDE BULLETIN FOR RESIDENCE OF FOREIGNERS -- TOURISM OPERATIONS -- SETTLEMENT OF TRAVEL TICKET -- HOW TO SUBMIT YOUR APPLICATIONS AND DOCUMENTS TO PASSPORT AND NATIONALITY DEPARTMENT IN THE INVESTMENT ORGANIZATION -- HOW CAN YOU OPEN AN ACCOUNT IN FOREIGN CURRENCY IN A BANK IN EGYPT -- D.LAW NO. 89/1960 CONCERNING ENTRY AND RESIDENCE OF ALIENS IN A.R.E. AND DEPARTURE OF ALIENS THEREFROM IT -- DISTRIBUTION AND TRANSFER OF PROFITS AND HE-EXPORT OF INVESTED CAPITAL -- THE TRANSFER OF THE NET PROFITS AND INVESTED MONEY -- LICENSING THE EXERCISE OF TRADES AND PROFESSIONS IN THE FREE ZONES,AND FREE ZONES ENTRY AND EXIT PERMITS -- Law No. 26/1975 CONCERNING EGYPTIAN NATIONALITY -- DECRLE NO. 31/1960 IN RESPECT OF VISAS -- D.NO 47/1974 FOR ESTABLISHING AN OFFICE FOR WORK PERMITS TO FOREIGNERS IN THE INVESTMENT AUTHORITY AND DEFINING ITS COMPETENCES -- D.NO. 179/1964 TRAVEL DOCUMENTS WHICH ARE ISSUED TO CERTAIN CATEGORIES OP FOREIGNERS